(untitled) (Academicia Globe: Inderscience Research, 2024)
This article focuses on further reducing the negative impact on the competitiveness of the republic’s economy by gradually reducing the monopoly in the commodity and financial markets, increasing the efficiency of the system of granting benefits and preferences, as well as reducing the regulatory system of legislation. Simplification of the mechanism of taxation of small and medium-sized business entities and implementation of tax administration and fundamental improvement of mutual cooperation of taxpayers in the fulfillment of republican tax obligations.